Tracking and Trajectory Analysis of Active Commuting from Childhood to Midlife - Yang, Xiaolin; Kukko, Tuomas; Salin, Kasper; Kulmala, Janne; Rovio, Suvi P.; Pahkala, Katja; Lehtimäki, Terho; Raitakari, Olli T.; Tammelin, Tuija H. (Ovid Technologies (Wolters Kluwer Health), 2025)
Purpose
To examine the tracking and trajectories of active commuting (AC) from childhood to midlife and their association with physical activity (PA) levels over 35 years.
Methods
Self-rated AC and PA data were extracted from the Young Finns Study across six phases (1983 − 2018) for tracking (n = 2851) and trajectories (n = 1220). Accelerometer-derived PA was quantified in 2018–2020 (n = 1134). AC tracking was analyzed using Spearman’s correlation, percentage agreements, and kappa statistics. Latent class analysis was used to identify distinct AC trajectories, and their associations with adult PA were subsequently evaluated.
Results
Tracking correlations of AC over 3 − 4, 6 − 7, 15, 18, and 35 years for both sexes were 0.40 − 0.43, 0.30 − 0.33, 0.25 − 0.32, 0.20 − 0.23, and 0.15 − 0.22 in summer, and 0.38 − 0.42, 0.35 − 0.41, 0.30 − 0.40, 0.25 − 0.33, and 0.23 − 0.31 in winter, respectively. Percentage agreements exceeded 54%, with kappa statistics ranging from slight to fair over time. Based on AC trajectories, four classes were identified for men (M) and five for women (W): stable car commuting (M:58.9%, W:37.4%), decreasing AC (M:16.5%, W:22.2%), increasing AC (M:12.8%, W:17.3%), and stable AC (M:11.8%), stable active walking (W:12.2%), and stable active summer cycling (W:10.8%). Compared to stable car-commuting ones, women who consistently walked or cycled in summer had higher adult moderate-to-vigorous PA and step counts. Men with consistent AC accumulated more steps and higher self-reported PA. Increasing AC in men also reported higher total PA. Stable AC participants were more physically active on weekdays, while men in the increased AC group were more active on weekends.
Conclusions
Tracking of AC from childhood to mid-adulthood was low to moderately high. Stable and increasing AC trajectories predicted higher adult PA levels during weekdays or weekends.